Analysis of the Spatio-Temporal Variation of the Thermal Pattern of River Ganges in Proximity to Varanasi, India - Das N.; Bhattacharjee R.; Choubey A.; Agnihotri A.K.; Ohri A.; Gaur S. (My University, 2025)
The temperature of a river is a fundamental aspect of its water quality and has a bearing on its ecosystem to a greater extent. Therefore, in systematic planning for optimal stream monitoring programs involving the determination of location at monitoring stations, understanding this crucial thermal parameter is much desired. This would help to give an integrated scenario regarding physical, chemical, and biological processes occurring in the river ecosystem. Water quality parameters of the river such as dissolved oxygen, pH, salinity get affected due to change in river thermal patterns. In this study, the Landsat-8 TIR sensor was used to study spatial and temporal variations of river temperature. Thermal bands of 23 cloud-free Landsat-8 images from June 2013 to November 2020 were processed to prepare thermal maps of a stretch of river Ganges at Varanasi, India. The work has been validated by in-situ temperature measurement with a portable thermal sensor having high accuracy (± 0.1 °C). A good correlation (R2 = 0.927 and RMSE = 0.956) was observed between the sensor's estimated temperature and the in-situ temperature. The results exemplify that water surface temperature at confluence points was relatively higher due to the incoming effluents than the mid-river temperature. The ‘confluence point 3’ has the least relative temperature variation. The relative temperature variation has been more prominent for the month of February in comparison to June and November. Owing to the time series data availability and worldwide coverage of the Landsat-8 satellite, the present work provides a promising strategy for studying the thermal patterns in other rivers. © 2022, Indian Society of Remote Sensing.